BLOCK SLOPE IS THE MAIN DETERMINANT OF BLOCK PHASE PERFORMANCE IN SWIMMING - ÖDEK,Uğur (2021)
ABSTRACT Introduction Swimming starts are an important component for decreasing the total race time, especially in short events. In this phase of swimming, the aim is to increase performance using many different techniques and starting platforms. Objectives The effects of height and slope of the starting block on kick-start performance were assessed in this study. Methods Six male competitive swimmers performed 24 kick-starts using four block settings: 65 cm & 75 cm flat and 65 cm & 75 cm sloped. Two-dimensional kinetic and three-dimensional kinematic data were analyzed, including average and maximum horizontal/vertical forces and impulses; reaction times; movement and block times; and take-off vertical/horizontal velocities. Two-way within-subject design ANOVAs were implemented to test the effects of block height and slope on the kinetic and kinematic variables. Results Block slope was the main factor affecting most of the dependent variables. Shorter block and movement times, greater average and maximum vertical forces, vertical impulse, and maximum horizontal force were found for the sloped settings. An inverse relationship was found between block height and 0-5 m times. Conclusion Based on the results, blocks with height of 75 cm and slope of 10° provided better results in swimmers’ performance in the block phase. Level of evidence II, Therapeutic Studies -Investigating the Results of Treatment